Merokok dan Oksidasi DNA - Fitria, Fitria; Triandhini, R.I.N.K Retno; Mangimbulude, Jubhar C.; Karwur, Ferry Fredy (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Cigarette smoke consists of a mix of chemical substances in the form of gases and dispersed particles. Recently, more than 4000 compounds presented incigarette smoke have been isolated. Most of these compounds are toxic to our body’s cells. Toxic gases including carbon monoxide (CO), hydrogen cyanide(HCN), nitrogen oxides, and volatile chemicals such as nitrosamines, formaldehyde are found in in cigarette smoke. besides toxic compounds, cigarettesmoke also containsfree radicalsincluding peroxynitrite, hydrogen peroxide, and superoxide. These free radicals may accelerate cellular damage due tooxidative stress. Targets od free radical attacks include DNA, protein and lipids. The harmful chemicals in form of gases and volatile substances in cigarettescause multiple genetic mutations. the combination of genetic mutations and DNA damage lead to genetic instability and it may cause cancer. OxidativeDNA damage caused by cigarette smoke can be identified with the presence of 8-oxoguanosine used as one of the biomarkers for oxidative DNA damage.Increased concentration of 8-oxoguanosine in DNA has an important role in carcinogenesis and triggers tumor cells. both active and passive smokers havebeen reported to have an elevated concentration of 8-oxoguanosine in their lung tissue and peripheral leukocytes as well as for passive smokers. This paperprovide informations and understanding of the effects of smoking on the genetic stability, especially in the DNA molecule.